PET performance evaluation of the small-animal Hyperion IID PET/MRI insert based on the NEMA NU-4 standard. (24th October 2018) - Hallen, Patrick; Schug, David; Weissler, Bjoern; Gebhardt, Pierre; Salomon, André; Kiessling, Fabian; Schulz, Volkmar
Abstract: The Hyperion II D PET insert is the first scanner using fully digital silicon photomultipliers for simultaneous PET/MR imaging of small animals up to rabbit size. In this work, we evaluate the PET performance based on the National Eletrical Manufacturers Association (NEMA) NU 4-2008 standard, whose standardized measurement protocols allow comparison of different small-animal PET scanners. The Hyperion II D small-animal PET/MR insert comprises three rings of 20 detector stacks with pixelated scintillator arrays with a crystal pitch of 1 mm, read out with digital silicon photomultipliers. The scanner has a large ring diameter of 209.6 mm and an axial field of view of 96.7 mm. We evaluated the spatial resolution, energy resolution, time resolution and sensitivity by scanning a 22 Na point source. The count rates and scatter fractions were measured for a wide range of 18 F activity inside a mouse-sized scatter phantom. We evaluated the image quality using the mouse-sized image quality phantom specified in the NEMA NU4 standard, filled with 18 F. Additionally, we verified the in-vivo imaging capabilities by performing a simultaneous PET/MRI scan of a mouse injected with 18 F-FDG. We processed all measurement data with an energy window of 250 keV to 625 keV and a coincidence time window of 2 ns. The filtered-backprojection reconstruction of the point source has a full width at half maximum (FWHM) of 1.7 mm near the isocenter and degrades to 2.5 mm at a radial distance of 50 mm. The scanner's average energy resolution is 12.7% (Δ E / E FWHM) and the coincidence resolution time is 609 ps. The peak absolute sensitivity is 4.0% and the true and noise-equivalent count rates reach their peak at an activity of 46 MBq with 483 kcps and 407 kcps, respectively, with a scatter fraction of 13%. The iterative reconstruction of the image quality phantom has a uniformity of 3.7%, and recovery coefficients from 0.29, 0.91 and 0.94 for rod diameters of 1 mm, 3 mm and 5 mm, respectively. After application of scatter and attenuation corrections, the air- and water-filled cold regions have spill-over ratios of 6.3% and 5.4%, respectively. The Hyperion II D PET/MR insert provides state-of-the-art PET performance while enabling simultaneous PET/MRI acquisition of small animals up to rabbit size.